Inter-Institutional Communication Model for Online Learning for Elementary School Students - Widodo, Aan; Akbar, Moh. Rifaldi; Nurhaliza, Wa Ode Sitti; Rony, Zahara Tussoleha (Mediator: Jurnal Komunikasi, 2023)
This study seeks to understand various communication events in the learning process holistically. The communication events in this paper include communication from the interpersonal level, computer-mediated communication, to organizational communication. This study explains the communication process from the human aspect (non-technical) and human relations with learning media technology (technical). This study seeks to answer how daily communication and communication media technology is vital in implementing online education for elementary school students. This study aims to offer an inter-institutional communication model that can be used to provide online education for students in elementary schools during disaster emergencies such as the Covid-19 pandemic. This study uses a focus group discussion (FGD) methodology with data collection techniques in interviews, field observations, and literature studies. This study uses data analysis in three-stage coding: open, axial, and selective. The subjects in this study were providers of elementary school (Sekolah Dasar) in Subdistrict (Kelurahan) Teluk Pucung, Kota Bekasi. This study finds that there is a need for intensification of communication from the daily level involving local stakeholders to resolve non-technical problems. The government needs to improve the communication media technology infrastructure and innovation in learning media technology for students who take online learning at the elementary level.